Gambaran Strategi Koping Orang Tua Pada Anak Yang Dirawat di Ruang Rawat Anak - Zidni Ilman Nafi'a; Siti Arifah (Universitas Pahlawan Tuanku Tambusai, 2026)
A child’s hospitalization often causes stress for parents due to the emotional burden, uncertainty, and role changes during the treatment process. Coping strategies play a crucial role in determining how parents manage this stress. This study aims to describe the coping strategies of parents whose children are hospitalized. This study employs a descriptive quantitative design with a cross-sectional approach. The sample consisted of 10 parents selected using purposive sampling based on inclusion criteria, namely parents of children aged 1–12 years who were undergoing inpatient care for at least 48 hours and were willing to participate as respondents and complete the questionnaire. Data were collected using the Brief COPE questionnaire, which consists of 14 items and a 4-point Likert scale. Data analysis was conducted using univariate methods to present frequency distributions, percentages, and mean values. The results indicated that most parents employed adaptive coping strategies such as religious coping, active coping, planning, emotional support, and seeking information. Meanwhile, maladaptive coping strategies such as self-blame and denial were found at low levels. These findings suggest that parents still require psychosocial support while their children are hospitalized. This study can serve as a basis for healthcare professionals in developing family-centered care interventions in pediatric wards.